Advances in the treatment of visual hallucinations in neurodegenerative diseases. (July 2013) - Collerton, Daniel; Taylor, John-Paul
Treatment of visual hallucinations in neurodegenerative disorders is not well advanced. The complexity of underlying mechanisms presents a number of potential avenues for developing treatments, but also suggests that any single one may be of limited efficacy. Reducing medication, with the careful introduction of antidementia medication if needed, is the mainstay of current management. Antipsychotic medication leads to excessive morbidity and mortality and should only be used in cases of high distress that do not otherwise respond. Education, reduction of risk factors and psychological treatments have limited evidence of efficacy, but are unlikely to cause harm.